A Rare Case of Hemophagocytic Lymphohistiocytosis Associated With Myelodysplastic Syndrome and Trisomy 8 in a Pediatric Patient. Issue 1 (January 2019) - Kim, Seh Hyun; Yi, Dae Yong; Lee, Na Mi; Yun, Sin Weon; Chae, Soo Ahn; Lim, In Seok
Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a rare disease resulting in clinical and biochemical manifestations of extreme inflammation. Myelodysplastic syndrome (MDS) represents a heterogenous group of clonal hematopoietic disorders. The development of MDS is common in children with trisomy of chromosome 8. Here, we report a fatal case of 8-year-old girl who was admitted to the emergency department with status epilepticus, and later diagnosed with HLH associated with MDS and trisomy of chromosome 8. We believe this is the first reported case of HLH associated with MDS and trisomy 8 in a pediatric patient.